Studying collective action - Eyerman, Ron.; Diani, Mario (Sage Publications, 1992)
"This original book is the first to concentrate on the methodological problems of studying collective action. How do social movements such as environmental concern, political protest or feminism emerge and operate? How can the researcher chart and analyse the process?" "In a lucid and coherent discussion ranging across Europe, the authors emphasize the link between theorization and data analysis. This crucial step in the research process is often ignored in contemporary debates, which tend to reduce methodological issues to the mechanics of research techniques." "The book illustrates the different research strategies that have developed to fit the theoretical and empirical peculiarities of research on collective action. These include both quantitative approaches, such as protest event analysis and network analysis, and qualitative approaches, such as political discourse analysis and life histories. The authors address problems of data construction, research design and operationalization of specific theoretical concepts. The impact on the research process of the relationship between researchers and researched is also assessed." "As an example of intelligent and reflective writing about the business of doing social research, Studying Collective Action will be of wide interest to students and lecturers in political science and sociology."--BOOK JACKET.
Includes bibliographical references and index.
Frontier land : collective action between actors and systems / Alberto Melucci.
The study of collective action : introductory remarks / Mario Diani and Ron Eyerman -- Support and mobilization potential for new social movements : concepts, operationalizations and illustrations from the Netherlands / Hanspeter Kriesi -- The case for longitudinal research on movement participation / Bert Klandermans -- Protest event data : collection, uses and perspectives / Dieter Rucht and Thomas Ohlemacher -- Analysing social movement networks / Mario Diani -- Political discourse analysis / Paolo R. Donati -- Life histories in the analysis of social movement activists / Donatella della Porta -- The rebellion of the research 'objects' / Hanspeter Kriesi -- Which side are you on? : reflections on methodological issues in the study of 'distasteful' social movements / Johanna Esseveld and Ron Eyerman.
"This original book is the first to concentrate on the methodological problems of studying collective action. How do social movements such as environmental concern, political protest or feminism emerge and operate? How can the researcher chart and analyse the process?" "In a lucid and coherent discussion ranging across Europe, the authors emphasize the link between theorization and data analysis. This crucial step in the research process is often ignored in contemporary debates, which tend to reduce methodological issues to the mechanics of research techniques." "The book illustrates the different research strategies that have developed to fit the theoretical and empirical peculiarities of research on collective action. These include both quantitative approaches, such as protest event analysis and network analysis, and qualitative approaches, such as political discourse analysis and life histories. The authors address problems of data construction, research design and operationalization of specific theoretical concepts. The impact on the research process of the relationship between researchers and researched is also assessed." "As an example of intelligent and reflective writing about the business of doing social research, Studying Collective Action will be of wide interest to students and lecturers in political science and sociology."--BOOK JACKET.
Available online through HathiTrust Emergency Access Service. Click the HathiTrust button on the right and log in to access this book online
Keywords: Mouvements sociaux. / ram; Sociologie / Recherche. / ram; Science politique / Recherche. / ram; Collectieve acties. / gtt; Soziale Bewegung / gnd; Kollektives Verhalten / gnd; Kollektives Handeln / gnd; Social movements / Research / Methodology.